A Netnographic Critique of Cultural Appropriation versus Cultural Competence in Digital Mental Health Ethnic Communities - Apriana Rahmawati; Suhendra Agung Wibowo; Beatriz Elizabeth Nuñez Martinez (Tarqabin Nusantara Group, 2026)
Background: Digital mental health campaigns increasingly incorporate local cultural symbols to improve engagement among ethnically diverse populations. However, whether these adaptations represent genuine cultural responsiveness or merely superficial branding remains unclear, particularly within Indonesia's multicultural context. This study explored how ethnic and indigenous communities interpret, contest, and reclaim the cultural authenticity of institutional digital mental health advocacy. Methods: A qualitative netnographic study was conducted through 24 weeks of non-participant observation across Indonesian- and Malay-language digital ecosystems, including institutional social media platforms, community-led discussion forums, and professional nursing and psychiatric networks. Public discussion threads were purposively sampled and analysed using reflexive thematic analysis to identify recurring patterns of community interpretation. Results: Four interrelated themes emerged: (1) tokenistic aesthetic inclusion, (2) decontextualisation of sacred healing practices, (3) community reclamation through counter-narrative production, and (4) a discursive transition from cultural competence toward cultural justice. Participants overwhelmingly perceived institutional campaigns as relying on symbolic cultural representation rather than meaningful collaboration, criticising the use of indigenous knowledge and cultural symbols without shared decision-making or reciprocal community benefit. Conclusion: Superficial visual and linguistic localisation alone does not meet communities' expectations of culturally safe digital mental health advocacy. The findings suggest that psychiatric nursing and digital health communication should move beyond conventional cultural competence frameworks toward culturally just approaches that prioritise community co-design, shared governance, equitable benefit-sharing, and recognition of indigenous epistemic authority in the development of digital mental health campaigns.